Collaboration behaviors within interactive exercise groups. Issue 9 (2nd September 2021) - McEwan, Desmond; Bennett, Erica V.; Rhodes, Ryan E.
Abstract: Objective: The purpose of this study was to gain a better understanding of collaboration behaviors within interactive exercise groups. Design: Qualitative study. Main Outcome Measures: Using semi-structured interviews, 16 individuals who exercise in small groups (e.g., workout partners, participants of interactive fitness classes) were recruited to (a) reflect on their experiences of collaboration within this context, and (b) identify behaviors that members demonstrate that help each other perform exercise tasks and achieve their exercise-related goals. Data were analyzed using thematic analysis. Results: We identified three overarching themes (and 14 subthemes) reflecting participants' perceptions and experiences of collaboration in exercise groups including 'motivation building', 'intragroup coaching', and 'personal support'. These collaboration behaviors were noted by participants as important in shaping their continued exercise adherence, enjoyment, and relatedness. Conclusion: This study advances knowledge of the specific ways in which individuals can work together effectively within interactive exercise groups and provides a novel means of understanding how the group environment might best be leveraged to support exercise behavior.